Flexible polypyrrole activated micro-porous paper-based photoanode for photoelectrochemical water splitting. (16th February 2021) - Thakur, Anupma; Kumar, Praveen; Mouli Thalluri, Sitaramanjaneya; Sinha, R.K.; Devi, Pooja
Abstract: We herein demonstrate polypyrrole decorated micro-porous laboratory filter paper (PFP) as photoanode (PA) for efficient and stable water splitting. The straddling band position with water redox and the measured band gap of 1.98 eV, make these PFP-PAs effective for water splitting reactions. The results manifest excellent photo-anodic PEC activity of these PFP-PAs, yielding a photocurrent density of 9.5 mA/cm 2 (at 1.23 V vs. RHE) in a three-electrode configuration. The incident photon-to-current efficiency (IPCE) and applied bias photon-to-current efficiency (ABPE) was measured to be 43.19% and 1%, respectively. Moreover, the robustness of these flexible PFP-PAs was visualized by the provided stability for more than 160 min in alkaline conditions. The current study provides a proof-of-concept for the realization of a cost-effective, flexible, and efficient paper-based artificial catalyst (like a natural leaf) for solar-driven water splitting. Graphical abstract: Image 1 Highlights: In-situ fabricated polypyrrole based flexible filter paper photo electrode (PFP-PEs). Exhibit a bandgap of 1.98 eV and reported as PEs for water splitting. Photocurrent density of 9.5 mA/cm 2 (at 1.23 V vs. RHE) in 3-electrode system. IPCE and ABPE was measured to be 43.19% and 1%, respectively. PFP-PEs stable for 160 min in alkaline conditions for PEC water splitting.